NPC1 deficiency in mice is associated with fetal growth restriction, neonatal lethality and abnormal lung pathology - Rodriguez-Gil, J; Watkins-Chow, D; Baxter, L; Yokoyama, T; Zerfas, P; Starost, M; Gahl, W; Malicdan, M; Porter, F; Platt, F; Paven, W (MDPI, 2019)
The rare lysosomal storage disorder Niemann-Pick disease type C1 (NPC1) arises from mutation of NPC1, which encodes a lysosomal transmembrane protein essential for normal transport and trafficking of cholesterol and sphingolipids. NPC1 is highly heterogeneous in both clinical phenotypes and age of onset. Previous studies have reported sub-Mendelian survival rates for mice homozygous for various Npc1 mutant alleles but have not studied the potential mechanisms underlying this phenotype. We performed the first developmental analysis of a Npc1 mouse model, Npc1em1Pav, and discovered significant fetal growth restriction in homozygous mutants beginning at E16.5. Npc1em1Pav/em1Pav mice also exhibited cyanosis, increased respiratory effort, and over 50% lethality at birth. Analysis of neonatal lung tissues revealed lipid accumulation, notable abnormalities in surfactant, and enlarged alveolar macrophages, suggesting that lung abnormalities may be associated with neonatal lethality in Npc1em1Pav/em1Pav mice. The phenotypic severity of the Npc1em1Pav model facilitated this first analysis of perinatal lethality and lung pathology in an NPC1 model organism, and this model may serve as a useful resource for developing treatments for respiratory complications seen in NPC1 patients.